(untitled) (Revista Iberoamericana de Bioética, 2025)
Shared decision-making has been gaining more space as it represents a conciliatory model between professional knowledge and the individual’s right to self-determination. This article proposes a debate on the use of shared decision-making for patients with dementia. Such patients tend to be considered incapable, and it is common to designate substitutes when decisions have to be made. However, there are consistent reports in the literature that patients are not unable to express needs and references. Several factors are highlighted as capable of influencing the greater or lesser involvement of these individuals, from the stage of the disease, characteristics of the caregiver, such as age and degree of kinship, and the type of decision to be made. The conclusion drawn is that shared decision-making can represent a powerful tool, offering the possibility for patients to exercise their personal autonomy, which will bring better outcomes for them and the professionals involved.